Assessment of the risk of discontinuation of tenofovir disoproxil fumarate after delivery and the benefit of continued treatment in patients with immune tolerance - Liang, Huan; Liang, Hengkai; Hu, Bobin; Huang, Long; Liang, Hongqian; Su, Minghua; Wang, Rongming; Su, Tumei; Li, Qingmei; Feng, Yanfei; Jiang, Jianning (Frontiers in Medicine, 2025)
BackgroundBoth domestic and foreign guidelines recommend that chronic hepatitis B virus (HBV) infection pregnant women in the immune tolerance phase (ITP) discontinue antiviral therapy after delivery, this study aimed to investigate the risk of postpartum drug withdrawal and the pros and cons of continuing treatment of tenofovir dipivoxil fumarate (TDF) in ITP pregnant women.MethodsThe study group consisted of 116 naive pregnant women in ITP, the control group included 81 naive chronic hepatitis B (CHB) pregnant women with HBeAg-positive and high viral load. The study aimed to compare the risk of discontinue rebound within 48 weeks postpartum, the antiviral efficacy and bone and renal safety of continuing TDF treatment until 144 weeks postpartum between the two groups.ResultsThere was no significant difference in the reduction of HBV DNA levels between the ITP group and the CHB group prior to labor (p < 0.05), with a 100% success rate in mother-to-child transmission prevention for both cohorts. Postpartum, 38.8% (45/116) and 18.5% (15/81) of parturients in the ITP group and CHB group, respectively, discontinued TDF at various time intervals. Comparative analysis of the risk of viral rebound within 48 weeks postpartum revealed no significant difference between the two groups (p > 0.05). The ITP group had higher rates of suboptimal response and low viremia occurrence compared to the CHB group (p < 0.05) at 48 weeks postpartum, but following salvage therapy up to 144 weeks postpartum, the cumulative rate of complete virological response(CVR) in the ITP group was non-inferior to that in the CHB group (p > 0.05). There were no significant differences in the average eGFR and serum phosphorus levels between the two groups from baseline to 144 weeks after TDF treatment.ConclusionPostpartum discontinuation of TDF poses significant risks for immunotolerant pregnant women, whereas continuing TDF treatment for 144 weeks postpartum demonstrates favorable antiviral efficacy, bone and renal safety profiles.